FOUNDING FAMILY OWNERSHIP AND FIRM PERFORMANCE: EMPIRICAL EVIDENCE FROM CONSUMER GOODS INDUSTRY IN INDONESIA - Margareta Bambang; Marko S. Hermawan (Bina Nusantara University, 2012)
This research investigates the significant influence of family ownership on firm performance in order to provide information to decision makers and other interested parties. The analysis includes comparisons between family and non-family firm performance in Indonesia. The samples are taken from 31 consumer goods companies, listed on the Indonesian Stock Exchange, ranging from 2005 to 2009. The results show that non-family firms perform better than family firms and no significant influence between family ownership and firms’ profitability. On the other hand, family ownership has negative contribution to firm market valuation. The study suggests that family firms have lower financial performance than that of non-family. Family members within the top position have major control rights and contribute a negative influence to firm performance. The evidence raises concerns about possible profit manipulation and weak governance law in Indonesia, and as a result there is an expropriation of wealth to the majority and family related shareholders.